Domain antibody downstream process optimization: High‐throughput strategy and analytical methods. Issue 2 (6th August 2015) - Welsh, John P.; Rauscher, Michael A.; Bao, Haiying; Meissner, Sandra; Han, InKwan; Linden, Thomas O.; Pollard, Jennifer M.
Abstract : Application of scale‐down high‐throughput screening has become integral for process development of antibody therapeutic products. In this work, methods are described for using high‐throughput techniques to develop a multicolumn chromatography purification protocol for a small domain antibody with very limited material (<200 mg). Screenings utilized resin slurry plates to explore and narrow potential operating space, and miniature columns were used to either confirm operating spaces or further explore impurity separations. Lab scale column confirmations were performed when appropriate. Affinity capture chromatography as well as ion exchange and multimodal polishing chromatography steps were explored. Feedstreams were pooled and recycled to preserve material for the different chromatography steps. Precise high‐throughput analytical assays were developed to fully characterize the domain antibody to a similar extent as a typical commercial therapeutic protein program. Optimized two‐column and three‐column processes provided overall chromatography yields of 66 and 58%, respectively, and were able to meet typical early phase requirements for removal of impurities such as aggregates, host cell protein, endotoxin, and other product‐related impurities. This study provides a comprehensive example of how a thorough biologics downstream process can be developed with a minimum of material.